"Is the friendship worth keeping:" Gender differences in communicating forgiveness in friendships. Issue 3 (27th May 2019) - Antony, Mary Grace; Sheldon, Pavica
Abstract : Although forgiveness plays an integral role in friendship maintenance, interpersonal communication scholarship has largely overlooked how transgressions and forgiveness are negotiated between friends. This study focuses on gender differences to develop a typology of relational transgressions in friendships. Two hundred and thirty survey respondents (116 women and 114 men) described relational transgressions in their friendships, the perceived severity of these transgressions, and strategies used to communicate forgiveness. A combination of MANCOVA and inductive analyses reveals gender differences. While male transgressions typically involve encroaching on other intimate relationships and theft, female transgressions emphasize disclosing personal communication beyond the friendship's boundaries. Conflicts between male friends could escalate from verbal to physical aggression, whereas female friends were likely to sabotage other close relationships that threatened the friendship. Finally, males preferred to communicate forgiveness using the minimizing strategy, while female friends generally favored the discussion and conditional forgiveness strategies. Overall, the perceived severity of a transgression was positively related to use of the discussion and conditional forgiveness strategies, and negatively related to the minimizing strategy. The implications of these findings are discussed.